Experiencing prayer: interpreting text and its context - Najah Nadiah Amran (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2016)
Performance of prayers are meaningful for the Muslim families as they indicate individuals and family religiousness. This article aims to highlight Western Muslim women religious experience dealing with Islamic texts. It focuses on daily prayer and the process of nurturing this practices in Muslim families. It intends to portray Muslim women’s primary concern especially in daily prayers still remained vital in promoting a sense of religious communities among the Western Muslims. In order to understand how Muslim women understand Islamic texts particularly hadith, this article analyse trend and reactions of western Muslim women on the obligation of nurturing prayers among Muslim children based on a selected hadith text. This article is an effort to investigate Islam from within by employing ethnography approaches; specifically participant observation and conversation. This article concludes that Islamic texts play major role in the life of Western Muslim women. In particular it discovers multiple trends of thinking among Muslim women in the Western context dealing with Islamic primary source.